2022
DOI: 10.1186/s13613-022-01046-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in patients who received veno-venous extracorporeal membrane oxygenation and renal replacement therapy: a retrospective cohort study

Abstract: Background Acute kidney injury (AKI) is a frequent complication in patients with severe respiratory failure receiving extracorporeal membrane oxygenation (ECMO). However, little is known of long-term kidney function in ECMO survivors. We aimed to assess the long-term mortality and kidney outcomes in adult patients treated with veno-venous ECMO (VV-ECMO). Methods This was a single-centre retrospective study of adult patients (≥ 18 years old) who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy in AKD stages not aligning with long-term outcomes can be attributed to the limitations of SCr as an acute illness kidney function marker. Haines et al 33 and Lumlertgul et al 34 have indicated that SCr values in the initial 3 to 6 months after discharge may not be as trustworthy. This unreliability is possibly due to the impact of acute skeletal muscle wasting on SCr, which may lead to kidney function overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of malnutrition is made by clinical observation or complementary testing. 28 The overall rate of receiving renal replacement therapy is 40-60% in ECMO patients, 29,30 however clinical practice fluctuates, and there is a strong correlation between mortality and renal replacement therapy as well as the mNUTRIC score. 18,31 In our study, we also found that the number of patients who received CRRT and the mNUTRIC score were significantly increased in the nonsurvival group compared to the survival group.…”
Section: Discussionmentioning
confidence: 99%